Influence of Collaborative Instructional Leadership of Principals and Teachers on Students’ Academic Performance in Secondary Schools in North Central, Nigeria - , Isah, J.; , Dr Agbe, J. I.; Dr Odeh, R. C.; Prof. Adelabu, S. B. (IJRDO- Journal of Educational Research, 2019)
Abstract - This study investigated the influence of collaborative instructional leadership of principals and teachers on students’ academic performance in secondary schools in North Central Nigeria. It was guided by three specific objectives and three research questions. Three hypotheses were formulated and tested at 0.05 level of significance. The study was hinged on McClelland’s Need Achievement Theory (1961) and Edwin Locke’s Goal-Setting Theory of Motivation (1960). The literature review conducted provided the roadmap of the gap to fill and the research design adopted. The study adopted a survey research design and the study area was North Central Nigeria. The population of the study was 16671, comprising 972 principals and 15699 teachers from 972 public secondary schools in the sampled states in North Central, Nigeria. The sample size for the study was 391 subjects, consisting of 36 principals and 355 teachers and it was drawn using Taro Yamen formula for sample size determination. The instrument used for data collection was structured questionnaire titled, “Influence of Collaborative Instructional Leadership on Students’ Academic Performance Questionnaire (ICILSAPQ)” constructed by the researchers. The study used Mean and Standard Deviation to answer the research questions while Chi-square statistic was used to test the hypotheses at 0.05 level of significance. The mean of 2.50 was used to arrive at the decision level for the research questions. The study found that jointly framing school goals, supervising instructions and protecting instructional time influence students’ academic performance in secondary schools in North Central Nigeria. The study recommended that principals and teachers be jointly involved in framing schools’ goals, supervising school instructions and protecting school instructional time as these would enhance students’ academic performance.